A perspective on green, blue, and grey spaces, biodiversity, microbiota, and human health. - Potter JD; Brooks C; Donovan G; Cunningham C; Douwes J (Elsevier B.V., 2023)
Humans have lived from equator to poles for millennia but are now increasingly intruding into the wild spaces of other species and steadily extruding ourselves from our own wild spaces, with a profound impact on: our relationship with the natural world; survival of other species; pollution; climate change; etc. We have yet to grasp how these changes directly impact our own health. The primary focus of this paper is on the beneficial influence of proximity to the natural environment. We summarize the evidence for associations between exposure to green space and blue space and improvements in health. In contrast, grey space - the urban landscape - largely presents hazards as well as reducing exposure to green and blue space and isolating us from the natural environment. We discuss various hypotheses that might explain why green, blue, and grey space affect health and focus particularly on the importance of the biodiversity hypothesis and the role of microbiota. We discuss possible mechanisms and exposure routes - air, soil, and water. We highlight the problem of exposure assessment, noting that many of our current tools are not fit for the purpose of understanding exposure to green and blue space, aerosols, soils, and water. We briefly discuss possible differences between indigenous perspectives on the nature of our relationship with the environment and the more dominant international-science view. Finally, we present research gaps and discuss future directions, particularly focusing on the ways in which we might - even in the absence of a full understanding of the mechanisms by which blue, green, and grey space affect our health - begin to implement policies to restore some balance to our environment of with the aim of reducing the large global burden of ill health.
Keywords: Aerosols; Air; Biodiversity; Biophilia; Blue space; Environmental microbiota; Exposure assessment; Green space; Grey space; Human ecology; Human health; Human microbiota; Indigenous perspective; Infectious diseases; Non-communicable diseases; Soil; Water; Humans; Soil; Biodiversity; Environmental Pollution; Microbiota; Parks, Recreational